2009
DOI: 10.1194/jlr.m800321-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of Abcd1 and Abcd2 genes sensitizes astrocytes for inflammation: implication for X-adrenoleukodystrophy

Abstract: X-linked adrenoleukodystrophy is a metabolic disorder arising from a mutation/deletion in the ABCD1 gene, leading to a defect in the peroxisomal adrenoleukodystrophy protein (ALDP), which inhibits the oxidation of very long chain fatty acids (VLCFAs). Thus, these VLCFAs accumulate. In a cerebral form of ALD (cALD), VLCFA accumulation induces neuroinflammation that leads to loss of oligodendrocytes and myelin, which ultimately shortens the lifespan. To establish a relationship between the metabolic disease and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
111
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(115 citation statements)
references
References 68 publications
3
111
0
1
Order By: Relevance
“…Other peroxisomal disorders are also associated with an increase in VLC-FA and VLC-PUFA in brain and plasma (69)(70)(71)(72)(73)(74)(75)(76)(77). Postmortem analyses of 4 day-to 5 monthold whole brains of Zellweger patients showed higher concentrations of VLC-PUFA than those found in normal brains ( 16 ).…”
Section: Nomenclature and Structure Of Vlc-fa And Vlc-pufamentioning
confidence: 99%
“…Other peroxisomal disorders are also associated with an increase in VLC-FA and VLC-PUFA in brain and plasma (69)(70)(71)(72)(73)(74)(75)(76)(77). Postmortem analyses of 4 day-to 5 monthold whole brains of Zellweger patients showed higher concentrations of VLC-PUFA than those found in normal brains ( 16 ).…”
Section: Nomenclature and Structure Of Vlc-fa And Vlc-pufamentioning
confidence: 99%
“…The Silencer siRNA (Ambion; Austin, TX) was used for Abcd1 and Abcd2 silencing in primary mouse astrocytes as described previously ( 19 ). The siRNAs were mixed and diluted in OPTI-MEM1 medium to a fi nal concentration of 30 nM/well.…”
Section: Lipid Extraction and Fa Analysismentioning
confidence: 99%
“…The peroxisomal oxidation of FAs in control, X-ALD fibroblasts, and SAHA-treated X-ALD fi broblasts was determined in 6-well plates as described previously ( 19 ). ␤ -Oxidation of FAs to acetate (water-soluble product) was determined using [1-14 C]-labeled FAs as substrate (C 24:0 , lignoceric acid, or C 16:0 , palmitic acid) (American Radiolabeled Co. ; St. Louis, MO), as described previously ( 52 ).…”
Section: Fa ␤ -Oxidationmentioning
confidence: 99%
“…Recently, Singh et al showed that silencing of the Abcd2 gene decreased the ratio of the C24:0/C16:0 β-oxidation activity, as the silencing of the Abcd1 gene had done, in mouse primary astrocytes. 32) Fourcade et al demonstrated that C26:0 β-oxidation activity in the cortical brain slices of Abcd2-deficient mice decreased to approximately 70% of the control. 31) It is thus possible that Abcd2 contributes to the abcd1-independent pathway in the case of mouse astrocytes.…”
Section: Discussionmentioning
confidence: 99%